2010
DOI: 10.1111/j.1743-6109.2010.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Experiences of Men with Incontinent Partners

Abstract: Introduction Several studies show that urinary incontinence (UI) impairs women’s sexual functioning and sexual satisfaction. However, there is no scientific knowledge about the effects of UI on sexual functioning of the male partners. Aim To analyze sexual functioning of the male partners of females with UI. Methods During a period of 2.5 years all new female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The mean total score from the Zarit Burden Interview, one of the most widely used tools to measure caregiver burden, was significantly higher among caregivers of patients who were incontinent than among those of patients who were continent. Male partners of women with urinary incontinence also report lower sexual function and sexual satisfaction 166 . Overall, female urinary incontinence and urgency negatively affect sexual function in almost 50% of affected women and in 20% of their partners 167 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…The mean total score from the Zarit Burden Interview, one of the most widely used tools to measure caregiver burden, was significantly higher among caregivers of patients who were incontinent than among those of patients who were continent. Male partners of women with urinary incontinence also report lower sexual function and sexual satisfaction 166 . Overall, female urinary incontinence and urgency negatively affect sexual function in almost 50% of affected women and in 20% of their partners 167 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Little is known about the male partner's perspective of women who undergo an antiincontinence procedure. Bekker et al 20 reported that male partners of women with SUI have diminished sexual function, lower frequency of intercourse, less sexual satisfaction, and more erectile dysfunction than men with continent partners. However, study including sexual satisfaction of patients' spouses after anti-incontinence surgery is currently limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, 1 study has shown that male partners of women with UI have diminished sexual function, lower frequency of intercourse, less sexual satisfaction, and more erectile dysfunction than men with continent partners. 18 …”
Section: Commentmentioning
confidence: 99%